2014
DOI: 10.1039/c3sm52697f
|View full text |Cite
|
Sign up to set email alerts
|

The fast dynamics of cavitation bubbles within water confined in elastic solids

Abstract: Many applications such as ultrasonic cleaning or sonochemistry use the ability of bubbles to oscillate and drive liquid flow. But bubbles have also received attention in porous media, where drying may cause cavitation, a phenomenon occurring in plant tissues. Here we explore the dynamics of cavitation bubbles when the liquid is fully entrapped in an elastic solid, using light scattering, laser strobe photography and high speed camera recordings. Our experiments show unexpectedly fast bubble oscillations in vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 26 publications
9
88
1
Order By: Relevance
“…A typical number of oscillation cycles, which follows from the quality factor, is on the order of 10 for R b /R c = 0.3. This value is in agreement with experimental measurements [14]. As a consequence, cavitation bubbles in confinements "ring" for a significant amount of time, which makes it possible to determine the frequency with sufficient accuracy.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A typical number of oscillation cycles, which follows from the quality factor, is on the order of 10 for R b /R c = 0.3. This value is in agreement with experimental measurements [14]. As a consequence, cavitation bubbles in confinements "ring" for a significant amount of time, which makes it possible to determine the frequency with sufficient accuracy.…”
Section: Discussionsupporting
confidence: 79%
“…2 were obtained at the following values of the physical parameters: ρ 0 = 1000 kg/m 3 , c = 1500 m/s, η = 0.001 Pa s, ρ s = 1233 kg/m 3 , c s = 2111 m/s, μ = 0.74 GPa, and R c = 100 μm. These values were chosen to reproduce cavitation experiments on transparent biomimetic wood [14,15]. Fig.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibration causing the acoustic emission remains to be resolved. One relevant hypothesis is a bubble vibration: indeed, within artificial wood in hydrogel, it was found that nucleated bubbles oscillate in volume for a few periods, at a megahertz frequency linked to the compression modulus of water and the surrounding matrix [27].…”
Section: Resultsmentioning
confidence: 99%
“…It is denoted as DV/V c ¼ p/K, where K is an effective elastic bulk modulus. Because water and wood volumes are stretched in series by the same pressure, the effective modulus is K ¼ 1/(1/K water þ 1/K c ) [26,27], with the compression modulus of water K water (2.2 GPa), and a volumetric elastic modulus K c G linked to the deformation of the material surrounding the cavity (G is the elastic shear modulus of the solid material surrounding the conduit). Here, we followed [28] and we used the value of K c ¼ 0.75 GPa, typical of conifers.…”
Section: Discussionmentioning
confidence: 99%